Enhanced Photodegradation of Dye Mixtures (Methyl Orange and Methyl Green) and Real Textile Wastewater by ZnO Micro/Nanoflowers - Kee, Ming Wei (2017)
Textile industry is the largest contribution of the dye pollutants towards the environment and its persistent nature due to their complex molecular structure poses severe environmental hazards. Among numerous proposed treatments, heterogeneous photocatalysis using zinc oxide (ZnO) has emerged as an effective mean for the degradation of dyes. In this study, ZnO micro/nanoflowers were fabricated via a PVPassisted co-precipitation method. As-synthesized ZnO micro/nanoflowers were characterized by XRD, FESEM, EDX, FTIR and PL analyses. The as-prepared ZnO was of the hexagonal wurzite phase with high crystallinity and it was observed to be a micro/nanoflower structure with an average diameters ranging from 890 nm to 1.261 µm. A possible formation mechanism of ZnO micro/nanoflowers was also suggested. The assynthesized ZnO was also indicated to be ZnO with ample amount of –OH groups on the surface of ZnO and low radiative recombination. The photocatalytic activity of ZnO micro/nanoflowers were tested in the degradation of methyl orange (MO) and methyl green (MG) mixtures under UV-vis light irradiation. Comparison studies were performed using commercial ZnO and as-synthesized ZnO and as-synthesized ZnO manifested superior photocatalytic performance. Moreover, sedimentation test was conducted and as-prepared ZnO showed better sedimentation performance due to high density of as-prepared ZnO. The optimal synthesis parameter was investigated to be ZnO PVP-12.5, whereas the best process parameters were determined to be 2.5 mg/L of MO and 5 mg/L of MG and solution pH of 6.5. 93.83 % of MO and 100 % of MG were viii degraded with 94.14 % of COD degradation efficiency within 240 minutes of irradiation. The degradation of real textile dye wastewater was also determined to be 75 % of COD degradation using as-synthesized ZnO micro/nanoflowers after 240 minutes of illumination.